An ATL78-Like RING-H2 Finger Protein Confers Abiotic Stress Tolerance through Interacting with RAV2 and CSN5B in Tomato - Song, Jianwen; Xing, Yali; Munir, Shoaib; Yu, Chuying; Song, Lulu; Li, Hanxia; Wang, Taotao; Ye, Zhibiao (Frontiers in Plant Science, 2016)
RING finger proteins play an important role in plant adaptation to abiotic stresses. In the present study, a wild tomato (Solanum habrochaites) cold-induced RING-H2 finger gene, ShATL78L, was isolated, which has been identified as an abiotic stress responsive gene in tomato. The results showed that ShATL78L was constitutively expressed in various tissues such as root, lea petiole, stem, flower, and fruit. Cold stress up-regulated ShATL78L in the cold-tolerant S. habrochaites compared to the susceptible cultivated tomato (S. lycopersicum). Furthermore, ShATL78L expression was also regulated under different stresses such as drought, salt, heat, wound, osmotic stress, and exogenous hormones. Functional characterization showed that cultivated tomato overexpressing ShATL78L had improved tolerance to cold, drought and oxidative stresses compared to the wild-type and the knockdown lines. To understand the underlying molecular mechanism of ShATL78L regulating abiotic stress responses, we performed yeast one-hybrid and two-hybrid assays and found that RAV2 could bind to the promoter of ShATL78L and activate its transcription, and CSN5B could interact with ShATL78L to regulate abiotic stress responses. Taken together, these results show that ShATL78L plays an important role in regulating plant adaptation to abiotic stresses through bound by RAV2 and interacting with CSN5B.